218 Divergent Clonal Evolution of Melanoma Brain Metastases in Response to Immunotherapy. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Alvarez-Breckenridge, Christopher; Stocking, Jackson; Lastrapes, Matt; Nayyar, Naema; Gill, Corey M; Bertalan, Mia; Kaplan, Alexander; McCabe, Devin; Horbinski, Craig; Zakaria, Rasheed; Nassiri, Farshad; Zadeh, Gelareh; et al.
Abstract: INTRODUCTION: Immune checkpoint blockade (ICB) has become first-line therapy for patients with metastatic melanoma due to success in controlling extracranial tumors. However, patients frequently experience discordant responses, with extracranial response and intracranial progression. It is well recognized that brain metastases undergo divergent evolution where extracranial and intracranial disease share a common genetic ancestor yet evolve independently. We hypothesize that ICB exerts selective pressure leading to the clonal evolution of treatment resistant clones that ultimately culminate in disease progression. METHODS: A cohort of 97 patients, encompassing 312 pre- and postimmunotherapy melanoma tumors, underwent whole exome sequencing (WES) and included primary, extracranial, or intracranial samples. Each tumor was analyzed for somatic mutations, copy number alterations, neoantigen profile, and patient-specific phylogenetic trees were constructed encompassing a tumor's genetic subclones. Heterogeneity of the tumor microenvironment was evaluated using high multiplicity single-cell immunofluorescent staining (CycIF). Single-cell sequencing was performed on fresh tissue from 12 patients with postimmunotherapy melanoma brain metastases using the Smart-Seq2 protocol. RESULTS: WES of pre- and postimmunotherapy tumors yielded distinct patterns of clonal evolution and immunoediting within brain metastases compared to their extracranial counterparts, including mutations in B2M and JAK2. CycIF demonstrated a trend toward decreased CD8 infiltration, increased FOXP3 and CD45RO suggesting less cytotoxic, terminally differentiated T cells in resistant tumors. Single-cell analysis of 3328 sequenced cells demonstrated patient-specific clustering and gene expression profiles mediating resistance to ICB. CONCLUSION: We document, for the first time, evidence of ongoing branched evolution during immunotherapy in brain metastases with divergence compared to systemic sites of disease. Next-generation sequencing provides novel insights into clonal evolution mediating discordant responses of intra- and extracranial sites and immunosuppressive features of the intracranial tumor microenvironment. Targeting these mechanisms of resistance provides potential therapeutic avenues for patients with progressive intracranial disease.